Carfilzomib, lenalidomide, and dexamethasone in patients with relapsed multiple myeloma categorised by age: secondary analysis from the phase 3 ASPIRE study. (17th February 2017) - Dimopoulos, Meletios A.; Stewart, A. Keith; Masszi, Tamás; Špička, Ivan; Oriol, Albert; Hájek, Roman; Rosiñol, Laura; Siegel, David; Mihaylov, Georgi G.; Goranova‐Marinova, Vesselina; Rajnics, Péter; Suvorov, Aleksandr; et al.
Summary: A primary analysis of the ASPIRE study found that the addition of carfilzomib to lenalidomide and dexamethasone (carfilzomib group) significantly improved progression‐free survival (PFS) compared with lenalidomide and dexamethasone alone (control group) in patients with relapsed multiple myeloma (RMM). This post hoc analysis examined outcomes from ASPIRE in patients categorised by age. In the carfilzomib group, 103/396 patients were ≥70 years old, and in the control group, 115/396 patients were ≥70 years old. Median PFS for patients <70 years old was 28·6 months for the carfilzomib group versus 17·6 months for the control group [hazard ratio (HR), 0·701]. Median PFS for patients ≥70 years old was 23·8 months for the carfilzomib group versus 16·0 months for the control group (HR, 0·753). For patients <70 years the overall response rate (ORR) was 86·0% (carfilzomib group) and 66·9% (control group); for patients ≥70 years old the ORR was 90·3% (carfilzomib group) and 66·1% (control group). Within the carfilzomib group, grade ≥3 cardiovascular adverse events occurred more frequently among patients ≥70 years old compared with patients <70 years old. Carfilzomib‐lenalidomide‐dexamethasone has a favourable benefit‐risk profile for patients with RMM, including elderly patients ≥70 years old. Trial Registration : clinicaltrials.gov identifier: NCT01080391.